No country for migrants?: critical perspectives on asylum, immigration, and integration in Germany - Zoungrana, Wilfried (Studies in critical social sciences, 2020)
"No Country for Migrants? Critical Perspectives on Asylum, Immigration, and Integration in Germany aims to critically contribute to ongoing debates about immigration, integration, and xenophobia in Germany. Set against the backdrop of Germany's controversial political decision to open its borders to refugees in 2015, the book realigns this watershed with the broader historical narratives of migration to explain its exceptionality both as an event and transformative force on the migration/integration discourse. The book further uses critical theories to make sense of the shifting socio-political coordinates of Germany. It addresses the history of Germany's migration policies, its soft and hard power in migration control, language and societal integration, immigration and the revival of right-wing extremism, as well as religion and immigration"--